Rozkład materialnego ciężaru dowodu w sprawach o zniesławienie - Liżyńska, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
In defamation proceedings there occurs the reversal of roles with regards to the distribution of the burden of proof. The defendant, in order to gain impunity of his or her actions, must prove that his or her pleas made to the prosecutor are true. And when we deal with defamation made publicly, when it does not apply to persons performing public functions, the defendant must also prove that the plea was used to achieve socially legitimate interests. The author presents de lege lata and de lege ferenda conclusions trying to answer the question of whether the reversal of the general principles of substantial burden of proof is justified.
Keywords: zniesławienie; ciężar dowodu; wykluczenie bezprawności; wina